2019
DOI: 10.1021/jacs.8b13248
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Lysine and Cysteine Reactivities for Designing Targeted Covalent Kinase Inhibitors

Abstract: Targeted covalent inhibitor design is gaining increasing interest and acceptance. A typical covalent kinase inhibitor design targets a reactive cysteine; however, this strategy is limited due to the low abundance of cysteine and acquired drug resistance from point mutations. Inspired by the recent development of lysine-targeted chemical probes, we asked if nucleophilic (reactive) catalytic lysines are common based on the published crystal structures of the human kinome. Using a newly developed pK a prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(179 citation statements)
references
References 50 publications
10
157
2
Order By: Relevance
“…A most recent study 53 demonstrated the capability of replica-exchange GBNeck2-CpHMD for accurate prediction of downshifted Cys and Lys pK a 's. Work is underway to benchmark the performance using single-pH simulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A most recent study 53 demonstrated the capability of replica-exchange GBNeck2-CpHMD for accurate prediction of downshifted Cys and Lys pK a 's. Work is underway to benchmark the performance using single-pH simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Although there remains much room for improvement, our present data are encouraging and demonstrate that single-pH simulations may be routinely performed on a desktop computer equipped with a single GPU card for a variety of applications, from assisting MD stimulations with protonation state assignment to offering pH-dependent corrections of binding free energies 10 and nucleophilic hot spots for covalent drug design. 53…”
Section: Discussionmentioning
confidence: 99%
“…All sidechains of Asp, Glu, His, Cys, and Lys were allowed to titrate, with their titration model parameters taken from our previous work. [28][29][30] An ionic strength of 0.15 M was used to represent the physiological salt condition. Simulations were run at a temperature of 300 K and an effectively infinite cutoff (999 Å) for nonbonded interactions.…”
Section: Methods and Protocolsmentioning
confidence: 99%
“…However, surface-exposed lysines are generally thought to be poor nucleophiles because they are protonated (p K a ~10.5) at physiological pH [ 100 ]. Recent studies using computational predictions suggest that localized p K a values may shift several units, allowing lysines to be amenable to reacting with electrophilic warheads [ 124 ]. Given the success of current covalent inhibitors targeting EGFR and BTK protein kinases, the future will likely see the development of new type VI inhibitors for treating disease.…”
Section: Part D: Type VI Kinase Inhibitorsmentioning
confidence: 99%